2015
DOI: 10.1021/acs.jpcc.5b02430
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of TiO2 Surface and Subsurface Oxygen Vacancy by the Screened Exchange Functional

Abstract: The formation energies of oxygen vacancies at different surface and subsurface sites of anatase (101), anatase (001) and rutile (110) surfaces are calculated by screened-exchange (sX) hybrid functional method. Our results show that the oxygen vacancy is more stable on the surface than subsurface for rutile (110), while it is more stable subsurface than on the surface for anatase surfaces. These results are similar to those found by simple density functional theory, but now the sX hybrid functional gives the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 44 publications
22
121
0
Order By: Relevance
“…For both the (001) and (101) facets, the order of Fermi level positions is ox-TiO 2 < st-TiO 2 < an-TiO 2 < sp-TiO 2 and is related to the different surface electronic structures due to the changed concentration of the different surface states of the different surfaces leading to band bending (space charge layer) effects. In addition, Li et al [19] found that O vacancies are shallow donors with a donor level even above the conduction band minimum at the (101) surface, whereas the donor level at the (001) surface is slightly lower in energy than the calculated gap. As Ti 3+ interstitial and O vacancy give rise to the localized impurity level below the lower end of the conduction band, the amount of these intrinsic defects as well as the surface termination is directly related to the Fermi level position.…”
Section: Facet Electronic Structurementioning
confidence: 97%
See 4 more Smart Citations
“…For both the (001) and (101) facets, the order of Fermi level positions is ox-TiO 2 < st-TiO 2 < an-TiO 2 < sp-TiO 2 and is related to the different surface electronic structures due to the changed concentration of the different surface states of the different surfaces leading to band bending (space charge layer) effects. In addition, Li et al [19] found that O vacancies are shallow donors with a donor level even above the conduction band minimum at the (101) surface, whereas the donor level at the (001) surface is slightly lower in energy than the calculated gap. As Ti 3+ interstitial and O vacancy give rise to the localized impurity level below the lower end of the conduction band, the amount of these intrinsic defects as well as the surface termination is directly related to the Fermi level position.…”
Section: Facet Electronic Structurementioning
confidence: 97%
“…[19] The surface states of the (001) facet near the bulk CBM are lower than those of the (101) facet. It was reported based on a theoretical calculation that the top surfaces of the (001) and (101) facets have surface states above the bulk VBM and below the bulk conduction band minimum.…”
Section: Facet Electronic Structurementioning
confidence: 98%
See 3 more Smart Citations